Managerial framing in light of discontinuous change: Revolutionists, evolutionists, and mediators - Daniel-Leonhard Fox; Oliver Kullik; Katharina Hölzle (Creativity and Innovation Management, 2024)
This study examines the critical role of middle and frontline managers in an incumbent organization navigating discontinuous change, emphasizing the balance between exploring new opportunities and exploiting existing ones. While top managers set the strategic ambidextrous direction, the on-the-ground manifestation and tension management fall predominantly to the middle and frontline managers. We introduce a novel typology, classifying these managers as Evolutionists, Revolutionists, or Mediators, each with distinct cognitive framings. Our findings underscore the importance of understanding and moderating these cognitive framings to facilitate successful ambidextrous implementation. Key managerial implications include the need for heightened awareness of tension points, strategic resource allocation, mitigation of extreme cognitive framings, and the significant value of Mediator managers in steering ambidextrous strategies. This research paves the way for a deeper understanding of individual-level ambidexterity and provides crucial insights for organizations to innovate in times of discontinuous change.
Keywords: 330; ambidexterity; case study; cognitive framing; discontinuous change; incumbent; tensions